The crystal structure of bis(4-chloro-2-(((2-chloroethyl)imino)methyl)phenolato-κ2N,O)-oxidovanadium(IV), C18H16Cl4N2O3V - Wei Wei; Zhang Ya-Zhai; Zhang Heng-Qiang; Zhang Qi-Ying; Xuan Zhao-Kun; Chen Hong-Li (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C18H16Cl4N2O3V, orthorhombic, Pbca (no. 61), a = 7.8555(3) Å, b = 21.6645(7) Å, c = 23.7584(8) Å, V = 4043.3(2) Å3, Z = 8, Rgt(F) = 0.0296, wRref(F2) = 0.0799, T = 296(2) K.